Pengaruh Konsentrasi HCl dan Waktu Fermentasi terhadap Kadar Bioetanol yang Dihasilkan dari Limbah Kulit Ubi Kayu (Manihot esculenta C.) - Sarmal (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2023)
A study has been carried out entitled the effect of HCl concentration and fermentation time on the levels of bioethanol produced from cassava peel waste (Manihot essculenta Crantz). This study aims to determine the effect of the length of fermentation time required to produce the optimum yield of bioethanol from the hydrolysis of glucose using HCl. The use of HCl as acid hydrolysis aims to hydrolyze cellulose and hemicellulose contained in cassava peels into simple monomers, namely glucose. The method used in this study is the experimental method. Based on the results of the research, the optimum bioethanol distillate yield obtained the 8th day fermentation time of 9,75%.